Praktik Quality Control Lapangan dalam Penguatan Kompetensi Pengawasan Konstruksi Mahasiswa Pendidikan Teknik Bangunan - Nisfuha Anindya, Dea; Muhammad Aris Ichwanto; Ahmad Yudi Mubarroq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of the construction industry requires students in the Building Engineering Education program to possess the construction supervision competencies needed in the workplace. However, students’ ability to understand the application of construction quality control in the field still requires direct hands-on field experience. This study aims to describe on-site Quality Control practices in strengthening the construction supervision competencies of Building Engineering students. The study employs a descriptive qualitative approach with four active students engaged in on-site Quality Control activities as subjects. Data were collected through field observations, interviews, and documentation of Quality Control checklists, and subsequently analyzed using the Miles and Huberman framework. The results of the study indicate that on-site Quality Control practices provide students with real-world experience in understanding the construction quality supervision process, enhancing their ability to analyze work, communicate, and adapt within the project environment. Student involvement in inspection activities alongside the Quality Control team strengthens their professional competencies in the field of construction supervision. Thus, on-site Quality Control practices can support students’ readiness to enter the professional construction workforce.